Interpersonal Meaning Realized in the Conversation Texts in English Textbook for Senior High School - Eni Fauziah Harahap (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2021)
This research examines the interpersonal meaning realized in the conversation texts in English Textbook for Senior High School Grade X. The purpose of this research is to describe the interpersonal meaning realized in the conversation texts in English Textbook. The interpersonal meaning that is analyzed namely the most dominant mood elements, residue elements and modality types. The design of the research was descriptive qualitative. The main sources of data in this research were the conversation texts realized in the English textbook. There were 58 conversation texts and 400 clauses gotten from those 58 texts that the researcher analyzed in this study. The results of data analysis showed that the interpersonal meaning realized in the conversation text: the most dominant Mood Types was declarative (298 clauses), then interrogative (94 clauses) and the least was imperative (11 clauses). While, the most dominant residue elements was complements are the highest dominant (329 clauses), then followed by predicators (246 clauses), the last was adjuncts (94).